ABC Animals - Bernthal;Mark (New Delhi Sterling, 1999)
From Alligator to Zebra, Barney takes children on an ABC tour of a wide variety of animals. The lively rhyme provides fun information about each animal. Also published as a readalong with a cassette, this book has not been widely available before on its own.